C–O-Selective Cross-Coupling of Chlorinated Phenol Derivatives - Russell, John E. A.; Neufeldt, Sharon R. (Synlett, 2021)
Chemoselective cross-coupling of phenol derivatives is valuable for generating products that retain halides. Here we discuss recent developments in selective cross-couplings of chloroaryl phenol derivatives, with a particular focus on reactions of chloroaryl tosylates. The first example of a C–O-selective Ni-catalyzed Suzuki–Miyaura coupling of chloroaryl tosylates is discussed in detail.1 Introduction2 Density Functional Theory Studies on Oxidative Addition at Nickel(0)3 Stoichiometric Oxidative Addition Studies4 Development of a Tosylate-Selective Suzuki Coupling5 Conclusion and Outlook
Keywords: nickel catalysis; cross-coupling; oxidative addition; chemoselectivity; density functional theory; Suzuki–Miyaura coupling